Interlacing via rational functions and spectral decomposition

First of all, I’d like to express my sympathies to everyone who is enduring hardships due to COVID-19. Stay well and be strong.

In this previous post, I discussed two important classical results giving examples of polynomials whose roots interlace:

Theorem 1: The roots of a real-rooted polynomial and its derivative interlace.

Theorem 2: (Cauchy’s interlacing theorem) The eigenvalues of a real symmetric matrix interlace with those of any principal minor.

In this post, I’d like to explain a general method, based on partial fraction expansions of rational functions, which gives a unified approach to proving Theorems 1 and 2 and deserves to be better known.

Interlacing and rational functions

Suppose p(x) = \prod_{j=1}^d (x - \alpha_j) and q(x) = \prod_{j=1}^{d-1} (x - \beta_j) are real-rooted polynomials. We say that the roots of p(x) and q(x) interlace if \alpha_1 \leq \beta_1 \leq \alpha_2 \leq \cdots \leq \beta_{d-1} \leq \alpha_d, and that they strictly interlace if strict inequalities hold throughout.

Theorem 3: Suppose \gamma > 0 and f(x) = \gamma \frac{q(x)}{p(x)}, where p(x) and q(x) are real-rooted polynomials of degree d and d-1, respectively. Then the roots of p(x) and q(x) interlace (rest. strictly interlace) if and only if f(x) = \sum_j \frac{\lambda_j}{x - \alpha_j} with \lambda_j \geq 0 (resp. \lambda_j > 0) for all j.

Proof (Sketch): We prove the strict case, assuming that the zeros of p(x) are simple; the general case follows by a continuity argument. Let \sum_j \frac{\lambda_j}{x - \alpha_j} be the partial fractions decomposition of f(x), and assume that \alpha_1 < \alpha_2 < \ldots < \alpha_d. If each \lambda_i > 0 then f'(x) < 0 for all x \not\in \{ \alpha_1,\ldots,\alpha_d \}. Since \lim_{x \to \alpha_j^+} f(x) = +\infty, \lim_{x \to \alpha_j^-} f(x) = -\infty for all j, and \lim_{x \to -\infty} f(x)=\lim_{x \to +\infty} f(x) = 0, it follows that f(x) has a unique root in (\alpha_{j-1},\alpha_j) for all j=2,\ldots,d and no other roots. Hence the zeros of p(x) and q(x) interlace. The converse is proved similarly.

Figure 1: In the left-hand plot, the zeros of p(x) and q(x) interlace. In the right-hand plot, they do not.

Interlacing of the roots of p(x) and p'(x)

Theorem 1, which asserts that the roots of p(x) and its derivative p'(x) interlace, is usually proved using Rolle’s theorem. We establish it here as a consequence of Theorem 3:

Proof of Theorem 1: Let f(x) = \frac{p'(x)}{p(x)}. Then f(x) = d\log p(x), so if p(x) = \prod_{j=1}^r (x - \alpha_j)^{m_j} with each m_j a positive integer, then f(x) = \sum_{j=1}^r \frac{m_j}{x - \alpha_j}. By Theorem 3, the zeros of p(x) and p'(x) interlace.

Spectral decomposition and the functional calculus

If A is an n \times n real symmetric matrix and \sigma(A) is the set of eigenvalues of A, then A has the well-known spectral decomposition A = \sum_{\lambda \in \sigma(A)} \lambda E_\lambda, where E_\lambda is the principal idempotent corresponding to orthogonal projection onto the eigenspace of \lambda.

More generally, we have the following result which is a special case of the so-called holomorphic functional calculus:

Theorem 4: If f(x) = \frac{q(x)}{p(x)} is a rational function which does not have a pole at any eigenvalue of A then f(A) := \sum_{\lambda \in \sigma(A)} f(\lambda) E_\lambda satisfies f(A) p(A) = q(A).

If f(x)=q(x) is a polynomial then Theorem 4 is proved in a number of standard linear algebra texts, and the general case follows by a suitable limiting argument.

In particular, applying Theorem 4 to f(x) = \frac{1}{c - x} we obtain the formula (cI - A)^{-1} = \sum_\lambda \frac{E_\lambda}{c - \lambda}. Since this is true for all c \neq \lambda, we obtain the following identity:

Corollary 5 (Spectral decomposition of the resolvent): (xI - A)^{-1} = \sum_\lambda \frac{(E_\lambda)}{x - \lambda}.

Cauchy’s interlacing theorem

Let A be an n \times n real symmetric matrix, and let B be the principal minor obtained by deleting row i and column i from A. Let \phi_A(x) (resp. \phi_B(x)) denote the characteristic polynomial of A (resp. B). By the cofactor formula for the inverse of a matrix, we have:

Lemma 6: (xI - A)^{-1}_{ii} = \frac{\phi_B(x)}{\phi_A(x)}.

Proof of Theorem 2: By Corollary 5 and Lemma 6, we have

(xI - A)^{-1}_{ii} = e_i^T (xI - A)^{-1} e_i = \sum_\lambda \frac{e_i^T E_\lambda e_i}{x - \lambda},

where e_i denotes the i^{\rm th} standard basis vector. Since

e_i^T E_\lambda e_i = \langle E_\lambda e_i, e_i \rangle = \langle E_\lambda^2 e_i, e_i \rangle = \| E_\lambda e_i \|^2 \geq 0,

the result now follows from Theorem 3.

Concluding remarks:

1. I learned Theorem 3 from this paper by McKee and Smyth, and I learned the proof of Theorem 2 that we’ve given here from Section 8 of the book Algebraic Graph Theory by Godsil and Royle.

2. For more details on the holomorphic functional calculus (which can also be used, for example, to define {\rm ln}(A) and \sqrt{A} when A has positive eigenvalues) and the spectral decomposition of the resolvent, see e.g. these notes by Rodica Costin or this Wikipedia page.

Leave a Reply

Fill in your details below or click an icon to log in: Logo

You are commenting using your account. Log Out /  Change )

Facebook photo

You are commenting using your Facebook account. Log Out /  Change )

Connecting to %s